PERSPEKTIF POLITIK HUKUM TERHADAP UNDANG-UNDANG NOMOR 19 TAHUN 2019 KOMISI PEMBERANTASAN KORUPSI - Putra, Afriansyah (Universitas Tadulako, 2024)
Africa Eradicating Corruption in Investigations: Using Normative Juridical Methods Referring to Seorjono Soekanto's typology, he explained that the study of normative legal approaches to normative ones conceptualizes law as norms, rules, regulations and legislation that apply at a certain time and place as a product of state power. certain sovereign. The main problem in this research is the political perspective of criminal law towards the Corruption Eradication Commission Law at the investigative level and the provisions that the Corruption Eradication Commission should use at the investigative level. If corruption cases do not involve law enforcement officials, state officials and other people who are related to criminal acts of corruption, it will disturb the public, especially regarding the issue of state losses. Law Enforcement of Corruption Crimes In practice, it faces various obstacles/obstacles, especially in optimizing the eradication of corruption. This is due to, among other things, the complexity of corruption cases, this requires coordinated handling but in reality if it is coordinated with the leadership of the party being investigated, the leadership concerned is not willing to have their work unit examined, also time constraints, the occurrence of corruption is generally a long time ago so it is difficult to prove it. . It is also possible that the evidence has been destroyed. This will make it difficult for investigators to look for evidence and witnesses and shed light on the perpetrators in the context of law enforcement. In order to enforce the law, law enforcement should not be indiscriminate and be able to apply the principles set out in the Instructions for Law Number 19 of 2019 of the Corruption Eradication Commission.